Pengaruh Media Video Pembelajaran untuk Meningkatkan Penerapan Prosedur Pada Materi Sub Tema Pola Gerak Dominan Senam di Kelas 5 SD - Bryan Decaprin; Yatim Riyanto; Andi Mariono (LP. Ma'arif Janggan Magetan, 2024)
The purpose of this study was to determine the increase in the application of student procedures after the use of learning video media on the sub-theme of the dominant movement pattern of grade 5 elementary school gymnastics. This study used a quantitative approach. The data used is taken from the value of the results of the front roll practice. The number of samples in this study was 25 grade 5 elementary school students. Data analysis technique using paired sample test. The results showed that there was a significant influence on the application of procedures after the use of learning video media.